Stable isotope hydrology in fractured and detritic aquifers at both sides of the South Atlantic Ocean: Mar del Plata (Argentina) and the Rawsonville and Sandspruit river catchment areas (South Africa). (January 2017) - Glok Galli, Melisa; Damons, Matthew E.; Siwawa, Sitembiso; Bocanegra, Emilia M.; Nel, Jacobus M.; Mazvimavi, Dominic; Martínez, Daniel E.
Abstract: The aim of this work is to characterize the isotope composition of water ( 2 H and 18 O) in order to establish the relationship between fractured and detritic aquifers in similar hydrological environments located at both sides of the Atlantic Ocean. The Mar del Plata zone, placed in the Argentine Buenos Aires province in South America, and the Rawsonville and Sandspruit river catchment areas, situated in the Western Cape province in South Africa were compared. Rainwater and groundwater samples from fractured and detritic aquifers were analyzed through laser spectroscopy. In both Argentina and South African study sites, stable isotopes data demonstrate an aquifers recharge source from rainfall. For the Mar del Plata region, two different groups of detritic aquifer's samples with distinct recharge processes can be identified due to the close relationship existing between the present hydrogeological environments, the aquifer's grain size sediments and the isotopes contents: one representing rapid infiltration in aquifer sediments of the creeks' palaeobeds and hills zones (sandy or silt sandy sediments) and the other with slow infiltration of evaporated water in plain zones with an aquitard behavior. In the last group, the evaporation process occurs previous infiltration or in the aquifer's non-saturated zone, because of the existence of very low topographic gradients and fine-grained sediments. The evaporation phenomenon is not evident in the Sandspruit river catchment site's detritic aquifer, because its sandy composition allows a faster infiltration rate than in the loess that compounds the Pampeano aquifer in the interfluves zones of the Argentinian study area. Highlights: Relationships between different aquifers' types are studied by using isotopic tools. Hydrogeological behavior similarities exist at both sides of the South Atlantic Ocean. Rain infiltration is the only aquifers' recharge mechanism. The distinct detritic aquifers' grain sizes give the difference between environments.